Transformasi Tata Ruang Rumah Warga Banjar Karang Dalem I, Desa Bongkasa Pertiwi, Kabupaten Badung, Bali - Prabawa, Made Suryanatha (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2021)
Badung Regency has declared 11 Badung Tourism Villages through Perbup no. 47 of 2010. 1 of the 11 Tourism Villages that have been proclaimed is Bongkasa Pertiwi Village (BP). The development of the number of tourist visits to BP village was quite significant before the pandemic. Along with increasing tourism activities in BP Village, there has been a transformation of the spatial layout of residents' houses that are able to accommodate the Homestay function (Tourism Accommodation). An in-depth study is needed, in order to find out to what extent the impact of BP Village's tourism development has affected the transformation of settlements, especially the private houses of its residents who are still traditional. The object of this research is Settlement Br. Karang Dalem I, which in terms of spatial settlements and private houses of residents, is very traditional. The purpose of this study was to explore, record, and analyze the spatial aspects of the settlement of Br. Karang Dalem I which is fairly unique (Typical/Traditional) along with the spatial impact of tourism developments that might affect these spatial aspects. This study will use an exploratory-qualitative method with cross-examination data analysis to obtain the best research conclusions. Based on the findings and results of the analysis, it can be concluded that the transformation occurs in the form of function adaptation but while maintaining the basic values of the traditional Balinese house layout.Keywords: Transformation; Layout; House; Traditional.